Foreign Policy and Geo-politics - Gautam, Shreedhar (NCWA Annual Journal, 2026)
Collective desire of people, national interest and economic prosperity are the basic factors behind defining foreign policy of most of the countries. Nepal’s foreign policy too, in principle, gives emphasis on meeting the aspirations of people and preserving the national independence and territorial integrity. In the light of emerging geo-political realities, Nepal needs to develop dignified relationship with the two immediate neighbouring countries on the win-win basis formula. However, in the present globalized world, it is not sufficient to confine our priorities to achieving a balance only with our nearest partners at a time when global powers are expanding their interest overtly or covertly to expand their sphere of influence. It is necessary to ensure that their assertive behaviour does not upend our basic principles that guide our national interest. So, framing a unanimous policy among the major parties is vital to safeguard the sovereignty of the country. This paper mainly focuses on the need of drastic change in our foreign policy approach and perspective to resist the unfriendly pressure and provocation that go against our national interest.